An investigation of the reciprocal relationship between cognitive style and political ideology - Yılmaz, Onurcan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
Although there are studies relating low-effort or intuitive thinking with political conservatism, there are no studies that systematically investigate the reciprocal relation between cognitive style and political ideology. In this research, we first examined the relation of analytic thinking style and political conservatism while controlling for demographic variables, need for cognitive closure, personality traits, religiosity and general cognitive ability (Study 1) and found that reduced analytic thinking predicts social conservatism and political identity but not economic or personal conservatism. In Study 2, we attempted to direct participants toward intuitive thinking by a cognitive load manipulation to see whether they would become more conservative as a result but a manipulation check indicated that the manipulation had failed. In Study 3, we gave a brief analytic thinking training and observed an increase in liberal opinions on a number of issues but no long term change in political attitudes. In Study 4, we attempted to test the reverse causal relation by directing participants toward liberalism or conservatism through passages arguing for the necessity of these political positions and seeing whether this would produce a shift in cognitive style but a manipulation check indicated that participants did not find the passages persuasive. Overall, the results indicate that social conservatives tend to think intuitively while liberals tend to think analytically and that being led to think more analytically increases social liberal (contextualized and less stable) opinions. Furthermore, the results suggest that people's long term political attitudes are resistant to experimental manipulations.
Keywords: Conservatism -- Turkey.